Simulating the hydrodynamics of an ROV using Fossen's model of hydrodynamics - Peh, Long Quan (Nanyang Technological University, 2023)
Remotely Operated Underwater Vehicles (ROV) are increasingly considered and deployed in different areas that are difficult for human to access, such as the deep sea. As these ROVs are subjected to hydro-environments, it is necessary to construct suitable simulators in order to test the feasibility of the ROV design in various water conditions before it is constructed and before it is deployed. This minimizes the costs and risks such as loss of the ROV. Hence, this project aims to begin the process of developing a suitable low cost simulator for the university with the concepts from Fossen’s Handbook of Marine Craft and Hydrodynamics. This paper goes through the experiments done using different simulators, the collection of data sets obtained from a simple experimental rig done at the university’s diving pool and also the import of the ROV model from Solidworks to Gazebo. Subsequent works which can be done to further the development of this simulator are also mentioned.